STRATEGI PEMASARAN KERUPUK UDANG KAYU API BAHAGIA DI KELURAHAN MENDAHARA ILIR KECAMATAN MENDAHARA KABUPATEN TANJUNG JABUNG TIMUR DITINJAU DARI PEMASARAN SYARIAH - Siti Rahmah; Habriyanto Habriyanto; Marissa Putriana (CV. Aksara Global Akademia, 2024)
This study aims to obtain data and information about developments and marketing strategies for happy firewood shrimp crackers in Mendahara Ilir Village, Mendahara District, Tanjung Jabung Timur Regency, supporting factors and marketing inhibiting factors, and marketing strategies for happy firewood shrimp crackers in Mendahara Ilir Village, Mendahara District. East Tanjung Jabung Regency in terms of shari'ah marketing. This research uses a kulitative research method. Data collection techniques through observation, interviews, and documentation. The data analysis technique uses qualitative data analysis based on marketing mix theory. The results of the study show that: (1) The sales of happy firewood shrimp crackers obtained in the last 5 years tend to decrease, namely from 2018 to 2022; (2) The strategy used by the seller to market the happy firewood prawn crackers by marketing them to stalls, opening stalls, and through direct marketing or promoting directly to neighbors; (3) The supporting factors in the strategy in marketing the happy firewood shrimp crackers in Mendahara Ilir Village, Mendahara District, East Tanjung Jabung Regency lie in the distinctive and tasty taste made from shrimp, the happy firewood shrimp crackers are durable, the raw materials are easily accessible and does not use hazardous materials in the production process and has received halal certification from the Indonesian Ulema Council, while the inhibiting factor for the happy firewood shrimp cracker marketing strategy lies in the packaging which still uses clear plastic and has not yet obtained a permit from the Food and Drug Supervisory Agency (BPOM). BPOM); (4) The marketing carried out by the seller of firewood prawn crackers is in accordance with the trade concept used by Rasulullah SAW, namely honesty, sincerity, hospitality, and advice. In addition, the marketing of happy firewood shrimp crackers is also in accordance with the characteristics of sharia marketing, namely theistic, ethical, realistic, and humanistic.